Hong Kong's Legislature under China's Sovereignty : 1998-2013. - Gu, Yu (Chinese and comparative law series., 2015)
In Hong Kong's Legislature Under China's Sovereignty: 1998-2013 Dr Gu Yu thoroughly analyses how Hong Kong's legislature has impacted the law-making process as well as the financial control and supervision of the executive branch of the government. The political cleavage in Hong Kong seen in recent years has affected the level of Legco's autonomy in terms of leadership, rules, committee autonomy and control over the legislative agenda. Given the weakened autonomy of Legco and the decline of moderate forces in both the pro-Beijing and pro-democracy camps, the role of Legco as a collective actor of checks and balances against the executive branch has been weakened. This book will appeal to both academics and practitioners whose work involves the relationship between the legislature and the executive branch in the HKSAR.